Monitoring the mobility of heavy metals and risk assessment in mine-affected soils after stabilization - Ahn, Yongtae; Han, Manho; Choi, Jaeyoung (ELSEVIER, 2020)
The geophysical and geochemical analytical methods were applied to monitor the status of mine-affected soils after stabilization. The resistivity of ASC(topsoil): 54.37 Omega-m, ASC(stabilized soil) : 34.77 Omega-m, ASC(subsoil): 147.83 Omega-m, the low resistivity in the stabilized soil. The chargeability was low in the sub soils with ASC(topsoil): 1.79 mV/V, ASC(stabilized soil): 1.97 mV/V, ASC(subsoil): 0.62 mV/V. The resistivity of GB(topsoil) : 32.11 Omega-m, GB(stabilized soil): 67.92 Omega-m, GB(subsoil): 121.20 Omega-m, the resistivity increased toward the bottom. The chargeability was high in the stabilized soils with GB(topsoil): 3.19 mV/V, GB(stabilized soil): 5.43 mV/V, GB(subsoil): 1.33 mV/V. The laboratory experiments and the two-dimensional imaging of field have good agreement with each measuring result. The dominant fraction of As and Pb was the residual fraction. The carcinogenic risk values for As were within the ranges of 6.38 x 10(-4) for Asangcheon (ASC), 4.51 x 10(-5) for Namsun (NS) and 3.14 x 10(-4) for Gunbuk (GB), respectively. The hazard quotient for non-carcinogenic risk was highest for As to children in ASC (1.417), NS (0.100) and GB (0.698), which covered approximately 94.7, 75.2 and 78.9 % of the hazardous indices, respectively.
Keywords: SPECTRAL INDUCED POLARIZATION; LEAST-SQUARES INVERSION; HUMAN HEALTH-RISK; RESISTIVITY; SEDIMENTS; SURFACE; BIOAVAILABILITY; EXTRACTION; ELEMENTS; ZINC